(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2010)
A new for science species of mosses Aulacomnium аrenopaludosum Boiko is described. The turfs are small, dense, yellow-green. The stem is erect, branched, rarely simple, to 0-,5-1,5 cm high. There are always many pseudopodia with leaf-like gemmae gathered together on their tops. Rhizoid tomentum is only in the lower part of a stem – up to 3-5 leaves, brownish. The leaves are decurrent (up to 7 cells), turned away only in the middle part – to 2/3 of length, in the top third are flat, with acuminate or integrate, unevenly cutting or toothed top. Rib does not reach a few cells up to the leaf top, sligthly enlarged at the base, becomes thinner to the top. Old leaves consist of more collenchyme cells. In the lower cornes of the leaf base, cells are not coloured, transparent, in old leaves only occasionally somewhat dirty-yellow coloured, often only one cell is coloured. Cells are situated in 1-3 rows along the leaf edge from leaf base upward. Vegetative propagation occurs by leaf-like gemmae. Sterile species, sporogonia are unknown. Collected from the southern vicinity of the Halytsynove village, Zhovtnevyi district, Mycolaivsky region and in Burcutska forest area, Golopristanskiy district of Khersonskaya region, Ukraine. The moss grows on plants’ remains in small marshes with Betula borysthenica Klokov and bush willows Salix sp. The new species differs from the close related species – Aulacomnium palustre (Hedw.) Schwaegr. и Aulacomnium androgynum (Hedw.) Schwaegr.– by stable characters with habitual similarity to Aulacomnium androgynum.